Nursing care to the intern child: teachers and students’ experiences and awarness - Beserra, Eveline Pinheiro; Lúcio, Ingrid Martins Leite; Cardoso, Maria Vera Lúcia Moreira Leitão (Rev Rene, 2007)
The aim of the present study was to describe a nursing care experience to the hospitalized child with focus on the teachers’ and students’ point of view. It took place in a pediatric unit of a public hospital in Fortaleza-CE, in May 2005. As a starting point we used the data from the student who was the main author of this report’s. field diary, and from which were gathered thoughts of the teacher’s’ point of view. This step was followed by the teaching-learning, procedures of motivational and non-motivational feelings and also by the development of interpersonal relationships between student-teacherpatient, student-family-team and student-student. The findings showed differences of opinion between the theory given in class and the reality of field practice. This research helped to ponder on the teacher’s role and the students’ preparation before engaging in a nursing care experience towards children.